1986
DOI: 10.1139/o86-033
|View full text |Cite
|
Sign up to set email alerts
|

Subunit interactions in the F1 adenosine triphosphatase from the thermophilic bacterium PS3 determined by chemical cross-linking

Abstract: Sone, N., Hou, C. & Bragg, P. D. (1986) Subunit interactions in the FI adenosine triphosphatase from the thermophilic bacterium PS3 determined by chemical cross-linking. Biochem. Cell Biol. 64, 229-237The arrangement of the subunits in TFI , the adenosine triphosphatase of the thermophilic bacterium PS3, has been investigated using bifunctional chemical cross-linking agents to covalently link adjacent subunits in the enzyme molecule. The cross-linked products resulting from the reaction of the enzyme with 2,2'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Earlier biochemical evidence has shown that a readily formed disulfide link between the EcF 1 ␦ and one of the ␣ subunits did not inhibit ATPase activity (44,45). Furthermore, with bifunctional cross-linking reagents, ␣-␦ dimers and ␣-␣-␦ trimers, but not ␤-␦ dimers, were identified in EcF 1 (46) and TF 1 (47). The formation of such dimers and trimers as well as b-␦ and b-b dimers have recently been observed by crosslinking of introduced cysteine residues in EcF 0 F 1 ␣, ␦, and b subunits (48,49).…”
Section: Discussionmentioning
confidence: 91%
“…Earlier biochemical evidence has shown that a readily formed disulfide link between the EcF 1 ␦ and one of the ␣ subunits did not inhibit ATPase activity (44,45). Furthermore, with bifunctional cross-linking reagents, ␣-␦ dimers and ␣-␣-␦ trimers, but not ␤-␦ dimers, were identified in EcF 1 (46) and TF 1 (47). The formation of such dimers and trimers as well as b-␦ and b-b dimers have recently been observed by crosslinking of introduced cysteine residues in EcF 0 F 1 ␣, ␦, and b subunits (48,49).…”
Section: Discussionmentioning
confidence: 91%